2014
DOI: 10.1371/journal.pone.0096277
|View full text |Cite
|
Sign up to set email alerts
|

Urban and Rural Safety Net Health Care System Clinics: No Disparity in HPV4 Vaccine Completion Rates

Abstract: ObjectiveSafety net health care centers in the US serve vulnerable and underinsured females. The primary aim of this work was to determine if HPV4 dosing compliance differs between females who receive doses at rural vs. urban core safety net health care locations.MethodsFemales exclusively receiving health care in the Truman Medical Center (TMC) safety net system at the urban core and rural locations were identified by their HPV4 vaccine records. Dates and number of HPV4 doses as well as age, gravidity, parity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Consistent with other recent research using samples from North Carolina [18] and safety net clinics [27], we found no metropolitan status differences in adolescent vaccination, on average. However, we extend the research in this area by finding important subgroups for which metropolitan status differences are significant and substantial.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with other recent research using samples from North Carolina [18] and safety net clinics [27], we found no metropolitan status differences in adolescent vaccination, on average. However, we extend the research in this area by finding important subgroups for which metropolitan status differences are significant and substantial.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is a paucity of research identifying factors that influence metropolitan status differences in actual HPV vaccination [5]. Studies that have examined these differences have been limited by the use of small data sets restricted to specific samples of girls or one specific geographic area [18, 22, 27]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation